Beauty Lia Entreprise / Wan Iffah Aida Wan Mohamad Isa...[et al.] - Wan Mohamad Isa, Wan Iffah Aida; Rosly, Nurizatul Lyana; Abdul Halim, Mohamad Ezmir; Amran, Muhammad Ammar; Roslan, Nurul Iqma Nasuhah (2020)
As a guideline for managing the business. First, and foremost, it should be used to help run your company with a more cohesive vision It is your roadmap. By truly analyzing your plan for marketing, sales, manufacturing, website design, etc., you greatly improve your chances for success.